Answer:
The graph in the attached figure
Step-by-step explanation:
we know that
The equation of the line in point slope form is equal to
[tex]y-y1=m(x-x1)[/tex]
we have
[tex]m=-\frac{3}{4}[/tex]
[tex]point\ (4,-5)[/tex]
substitute
[tex]y+5=-\frac{3}{4}(x-4)[/tex]
Convert to slope intercept form
[tex]y=mx+b[/tex]
isolate the variable y
[tex]y+5=-\frac{3}{4}x+3[/tex]
[tex]y=-\frac{3}{4}x+3-5[/tex]
[tex]y=-\frac{3}{4}x-2[/tex]
Find the intercepts
Find the y-intercept (value of y when the value of x is equal to zero)
For x=0
[tex]y=-\frac{3}{4}(0)-2=-2[/tex]
The y-intercept is (0,-2)
Find the x-intercept (value of x when the value of y is equal to zero)
For y=0
[tex]0=-\frac{3}{4}x-2[/tex]
[tex]x=-\frac{8}{3}=-2.667[/tex]
The x-intercept is (-2.667,0)
To graph the line plot the intercepts and join the points
see the attached figure